Identifying creditworthiness criterions and financing approval process of Islamic banks in Indonesia - Muhammad, Imaduddin; Sharofiddin, Ashurov (Springer Nature Switzerland AG, 2021)
The study aims to identify the creditworthiness criteria and approval factors in providing financing facilities to corporate and commercial clients of Islamic banks in Indonesia. It also explores the financing approval process in the Islamic bank for this segment. It employs the qualitative study of in-depth and semi-structured interviews method via the available online tool. The study selects 3 (three) Islamic bank officers from the different banks as the respondents. The study finds that the 5Cs elements are all important by emphasizing properly fixed asset collateral and the sound capacity of the clients. There is a typical internal approval process with the timing is different between each bank. It highlights the importance of financial covenants and the requirement to use CASA products. The study also reveals that the covid-19 pandemic has impacted the client’s business and its ability to repay the banks. The strategy is to conduct relaxation, reprofiling, and restructuring of the client’s facilities as per guideline from the regulator